Recent updated aspects of colicins of Enterobacteriaceae - Cursino,Luciana (2002)
The colicins are protein compounds produced by, and active against, Escherichia coli and others members of Enterobacteriaceae family. At least 34 different colicins have been described and found to share an interesting number of features. In the present review we focus on the major characteristics of colicins of gram-negative bacteria and explore their production and practical applications.The colicins are protein compounds produced by, and active against, Escherichia coli and others members of Enterobacteriaceae family. At least 34 different colicins have been described and found to share an interesting number of features. In the present review we focus on the major characteristics of colicins of gram-negative bacteria and explore their production and practical applications.